Macrochimerism in Intestinal Transplantation: Association With Lower Rejection Rates and Multivisceral Transplants, Without GVHD. Issue 10 (18th May 2015) - Zuber, J.; Rosen, S.; Shonts, B.; Sprangers, B.; Savage, T. M.; Richman, S.; Yang, S.; Lau, S. P.; DeWolf, S.; Farber, D.; Vlad, G.; Zorn, E.; et al.
Abstract : Blood chimerism has been reported sporadically among visceral transplant recipients, mostly in association with graft‐vs‐host disease (GVHD). We hypothesized that a higher degree of mixed chimerism would be observed in multivisceral (MVTx) than in isolated intestinal (iITx) and isolated liver transplant (iLTx) recipients, regardless of GVHD. We performed a longitudinal prospective study investigating multilineage blood chimerism with flow cytometry in 5 iITx and 4 MVTx recipients up to one year posttransplant. Although only one iITx patient experienced GVHD, T cell mixed chimerism was detected in 8 out of 9 iITx/MVTx recipients. Chimerism was significantly lower in the four subjects who displayed early moderate to severe rejection. Pre‐formed high‐titer donor‐specific antibodies, bound in vivo to the circulating donor cells, were associated with an accelerated decline in chimerism. Blood chimerism was also studied in 10 iLTx controls. Among nonsensitized patients, MVTx recipients exhibited greater T and B cell chimerism than either iITx or iLTx recipients. Myeloid lineage chimerism was present exclusively among iLTx and MVTx (6/13) recipients, suggesting that its presence required the hepatic allograft. Our study demonstrates, for the first time, frequent T cell chimerism without GVHD following visceral transplantation and a possible relationship with reduced rejection rate in MVTx recipients. Abstract : This study shows the presence of peripheral blood macrochimerism, which can be long‐lasting in the absence of graft‐versus‐host disease in intestinal transplant recipients, and an association between T cell macrochimerism and lack of significant rejection, which occur more frequently in multivisceral than isolated intestinal transplant recipients.